La influencia de los medios de comunicación que llevó al FREPAP a pasar la valla electoral en las elecciones congresales Perú 2020 - Castañeda, Andrea (2021)
The main objective of this academic article is to demonstrate the different strate gies used by the religious group and political party to reverberate in the hatred of the Peruvian population and retain loyalty of a large number of voters in the 2020 voting period. These different actions also led, consequently, the political party to overcome the electoral fence during the congressional elections that took place at the beginning of this year. The different reactions that users had regarding the contents made and subsequently viralized about the FREPAP political party will be evaluated. Along with this, the different points of view and harsh opinions held by many users about this religious group and now a member of Congress were evidenced; Once all this has been done, it will be possible to evaluate and demons trate how the media influenced the decision of the voters when voting for FREPAP.